Regulation of inositol 1, 4, 5-trisphosphate-induced Ca2+ release from the endoplasmic reticulum by AMP-activated kinase modulators. (January 2019) - Arias-del-Val, Jessica; Santo-Domingo, Jaime; García-Casas, Paloma; Alvarez-Illera, Pilar; Núñez Galindo, Antonio; Wiederkehr, Andreas; Fonteriz, Rosalba I.; Montero, Mayte; Alvarez, Javier
Graphical abstract: Highlights: The AMPK activator A769662 inhibited ER-Ca 2+ -release mediated by the IP3 R. The AMPK inhibitor dorsomorphin activated ER-Ca 2+ -release mediated by the IP3 R. Our data suggest that AMPK negatively regulates IP3 R. Phosphoproteomic data suggests some candidates to mediate IP3 R modulation. Abstract: The 5' AMP-activated protein kinase (AMPK) is a nutrient-sensitive kinase that plays a key role in the control of cellular energy metabolism. We have explored here the relationship between AMPK and Ca 2+ signaling by looking at the effect of an AMPK activator (A769662) and an AMPK inhibitor (dorsomorphin) on histamine-induced Ca 2+ -release from the endoplasmic reticulum (ER) in HeLa cells. Our data show that incubation with A769662 (EC50 = 29 μM) inhibited histamine-induced Ca 2+ -release from the ER in intact cells, as well as inositol-1, 4, 5-trisphosphate (IP3 )-induced Ca 2+ release in permeabilized cells. On the contrary, dorsomorphin (EC50 = 0.4 μM) activated both histamine and IP3 -induced Ca 2+ -release and reversed the effect of A769662. These results suggest a direct effect of AMPK regulation on IP3 receptor (IP3 R) function. A phosphoproteomic study did not reveal changes in IP3 R phosphorylation, but showed significant changes in phosphorylation of proteins placed upstream in the IP3 R interactome and in several proteins related with Ca 2+ metabolism, which could be candidates to mediate the effects observed. In conclusion, our data suggest that AMPK negatively regulates IP3 R. This effect constitutes a novel and very important link between Ca 2+ signaling and the AMPK pathway.